A new occurrence species Didissandra C. B. Clarke (Gesneriaceae Dumort) of the flora of Vietnam - Phuong, Vu Xuan; Xuyen, Do Thi (Academia Journal of Biology, 2012)
According to W. T. Wang, K. Y. Pan, Z. Y. Li, A. L. Weitzman & L. E. Skog, 1998, the genus Didissandra C. B. Clarke had about 30 species mainly distributed S.-E. Asia. There were 5 Didissandra species in Vietnam. During the study of specimen and documents of Gesneriaceae of Vietnam, we have found one new occurrence species of Didissandra: D. sinica for the flora of Vietnam, before is recorded endemic to China. D. sinica is shrubs to subshrubs. Stems glabrous to sparsely puberulent in young part. Leaf blade with both surfaces glabrous. Cymes 1-5-flowered. Bracts 1-2 ´ 0.5 mm, margin entire. Calyx 5-sect from base, segment 2.5-3 ´ 1 mm, glabrous. Corolla white or reddish, 1.2-1.5 cm long. Pistil 6-8 mm long. Ovary glabrous. Style 1.5-2 mm long, sparsely glandular puberulent. Capsule 2-5 cm long, glabrous. It closes to D. annamensis but differ as peduncle of general inflorescences very short, under 1 cm long; corolla white or reddish, 1.2-1.5 cm long, meanwhile D. annamensis has peduncle of general inflorescences long, upper 5 cm long; corolla blue, 3-4 cm long. Voucher specimens were collected in  Bac Son district, Lang Son province, and deposited in the Herbarium of the Institute of Ecology and biological Resources, Hanoi, Vietnam (HN).